2017
DOI: 10.1039/c6cc08512a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast chiral separations for high throughput enantiopurity analysis

Abstract: Recent developments in fast chromatographic enantioseparations now make high throughput analysis of enantiopurity on the order of a few seconds achievable. Nevertheless, routine chromatographic determinations of enantiopurity to support stereochemical investigations in pharmaceutical research and development, synthetic chemistry and bioanalysis are still typically performed on the 5-20 min timescale, with many practitioners believing that sub-minute enantioseparations are not representative of the molecules en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 42 publications
0
79
0
2
Order By: Relevance
“…The renewed interest in the SFC analytical field concurs with the introduction of third‐generation SFC instruments (around 2010) able to be used with commercial UHPLC packed columns (sub‐2 μm FPP or sub‐3 μm SPP) . While a pioneering sub‐minute chiral SFC separation was reported as early as in 1993 , only in the last years several groups have developed widely accessible SFC methods based on UHPLC CSPs leading to highly efficient separations of enantiomers in the second time scale . Hamman et al.…”
Section: Enantioselective Ultra‐high‐performance Sfcmentioning
confidence: 99%
“…The renewed interest in the SFC analytical field concurs with the introduction of third‐generation SFC instruments (around 2010) able to be used with commercial UHPLC packed columns (sub‐2 μm FPP or sub‐3 μm SPP) . While a pioneering sub‐minute chiral SFC separation was reported as early as in 1993 , only in the last years several groups have developed widely accessible SFC methods based on UHPLC CSPs leading to highly efficient separations of enantiomers in the second time scale . Hamman et al.…”
Section: Enantioselective Ultra‐high‐performance Sfcmentioning
confidence: 99%
“…Since the recent development of superficially porous particles or core‐shell particles, which offer high throughput and more effective separations, several studies have been explored using core‐shell macrocyclic glycopeptide‐based CSPs (TeicoShell [TS] and VancoShell [VS]) . This has been particularly useful to ultrafast chiral separations needed in second dimension (2D) LC . However, many glycopeptides are costly and have limited availability, which has led to a need to understand the applicability and limitations of more available glycopeptides so further exploration can be made concerning useful modifications.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] This has been particularly useful to ultrafast chiral separations needed in second dimension (2D) LC. [24][25][26][27][28][29] However, many glycopeptides are costly and have limited availability, which has led to a need to understand the applicability and limitations of more available glycopeptides so further exploration can be made concerning useful modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies of enantioselective separations have been showed that both SFC and HPLC provide good selectivity; however, the advantage of SFC over HPLC occurs in terms of flow rate, resolution, time of analysis, consumption of solvent, and high throughput . Thus, the SFC has been used not only for purification purpose, but also for method development and screening of chiral and achiral compounds in different matrices …”
Section: Introductionmentioning
confidence: 99%
“…1,8,9,11 Thus, the SFC has been used not only for purification purpose, but also for method development and screening of chiral and achiral compounds in different matrices. 12,13 Therefore, in this work these two techniques were employed for the chiral separation of β-hydroxy-1,2,3triazoles, 14 which are an important class of heterocyclic compounds obtained only by synthetic methodologies. These compounds have been extensively studied as potential targets for drug discovery since they possess a broad range of biological properties, including antimicrobial, antiviral, antiepileptic, anti-HIV and activities against several neglected diseases.…”
Section: Introductionmentioning
confidence: 99%